Pertanggungjawaban Pidana Nakhoda Kapal Asing Terhadap Pelanggaran Hukum di Wilayah Teritorial Indonesia - Eko Budi S (Universitas Batanghari Jambi, 2021)
As a very large archipelagic country, Indonesia is very strategically located on world trade routes, making Indonesian waters have several problems including problems of maritime environmental pollution and shipping safety. This problem is due to the presence of oil from ships, either from fuel, from the engine room or oil as cargo that pollutes the marine environment. This study aims to determine the criminal responsibility of foreign ship captains who have violated the rules regarding the protection and management of the maritime environment and shipping in Indonesia, while the benefit of this research is to increase understanding for users of Indonesian archipelagic sea lanes so that they can sail safely and safely. The research method used is normative juridical while solving the problem with a concept approach and case approach to analyze the Batam District Court Decision Number 234/Pid.Sus/2021/PN. Btm is related to the implementation of criminal liability for foreign ship captains who violate the law in the Indonesian territory. The result of this research is that foreign ship captains can be held accountable for violating the law based on the principles of criminal law applied in Indonesia. So it can be concluded that a foreign ship captain who has made a mistake can be punished and accounted for his actions because there are criminal elements that are fulfilled and proven to have violated the law in the Indonesian territory.